KOLABORASI GURU DAN ORANG TUA DALAM MENGEMBANGKAN ASPEK MORAL AGAMA ANAK USIA DINI (STUDI DI RA TIARA CHANDRA YOGYAKARTA) - Muammar Qadafi (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2019)
AbstractThe success of early childhood education cannot be separated from the role of teachers and parents. The teacher is the key to the success of students at school and parents as the key to success when theya are at home. This research is a qualitative research. The purpose of this study was to find out how is the collaboration between teachers and parents in developing the moral and religious aspects of early childhood at RA Tiara Chandra Yogyakarta. The results showed that the school had several programs with parents’ involvement, such as: parenting, whatsapp group, training in living values education, value-based social services, the cards of great children's habit, distribution of students’ report, and value performances at graduation day. The teacher also used several methods in learning activities in school, such as: exemplary, habituation, role playing, and storytelling. Students experience many changes in the internalization and practice of the moral and religious values when teachers used living good moral and religious values method and collaboration between teachers and parents run well. The supporting factors are the support of principals, teachers, and parents. While the inhibiting factor is the lack of awareness of parents to be involved in school activities and become role models at home. Key words: collaboration, teachers and parents, moral and religious AbstrakKesuksesan pendidikan anak usia dini tidak dapat dilepaskan dari peran guru dan orang tua. Guru merupakan kunci keberhasilan siswa saat berada di sekolah dan orang tua sebagai kunci keberhasilan saat berada di rumah. Penelitian ini merupakan penelitian kualitatif. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana kolaborasi antara guru dan orang tua dalam mengembangkan aspek moral agama anak usia dini di RA Tiara Chandra Yogyakarta. Hasil penelitian menunjukkan bahwa sekolah memiliki beberapa program yang melibatkan orang tua, yaitu: parenting, whatsapp group, pelatihan living values education, bakti sosial berbasis nilai, pembuatan kartu anak hebat, pembagian rapor, dan pentas nilai pada saat graduation day. Guru juga menggunakan beberapa metode pada saat kegiatan bermain di sekolah yaitu: keteladanan, pembiasaan, main peran, dan bercerita. Siswa mengalami banyak perubahan dalam internalisasi dan pengamalan nilai moral agama pada saat guru menggunakan metode yang berupa pengamalan nilai-nilai kebaikan dan kolaborasi guru dan orang tua berjalan dengan baik. Adapun faktor pendukungnya yaitu adanya dukungan kepala sekolah, guru, dan orang tua. Sedangkan faktor penghambat yaitu kurangnya kesadaran orang tua untuk terlibat dalam kegiatan sekolah dan menjadi role model ketika berada di rumah. Kata Kunci: kolaborasi, guru dan orang tua, moral agama